2014
DOI: 10.1103/physrevlett.113.243001
|View full text |Cite
|
Sign up to set email alerts
|

Breakdown of the Dipole Approximation in Strong-Field Ionization

Abstract: We report the breakdown of the electric dipole approximation in the long-wavelength limit in strong-field ionization with linearly polarized few-cycle mid-infrared laser pulses at intensities on the order of 10¹³ W/cm². Photoelectron momentum distributions were recorded by velocity map imaging and projected onto the beam propagation axis. We observe an increasing shift of the peak of this projection opposite to the beam propagation direction with increasing laser intensities. From a comparison with semiclassic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

13
196
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(209 citation statements)
references
References 43 publications
13
196
0
Order By: Relevance
“…3 (b). The laser field is linearly polarized and the wavelength is 3400 nm, as used in the experiment [10]. Similar to Fig.…”
mentioning
confidence: 69%
See 2 more Smart Citations
“…3 (b). The laser field is linearly polarized and the wavelength is 3400 nm, as used in the experiment [10]. Similar to Fig.…”
mentioning
confidence: 69%
“…3 (b) presents p z while Ref. [10] presented the peak offset of the photoelectron longitudinal momentum distribution. The calculated peak shift of the photoelectron longitudinal momentum distribution as a function of the laser intensity is shown in the supplemental file [27].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently it has been suggested that nondipole effects may play a role in strong-field ionization [70]. While such effects have been studied recently [71,72] showing a small shift in the photoelectron momentum distributions in the propagation direction (less than 0.025 atomic units in momentum) for ionization of atoms by a 3.4-μm laser at intensity of about 10 14 W/cm 2 or lower, due to the presence of the Lorentz force when nondipole effects are included, such a small shift has no direct consequence on the total ionization probability, which is the concern of this article. The main challenge in strong-field experiments is the characterization of laser intensity and its distribution within the focused volume.…”
Section: Discussionmentioning
confidence: 99%
“…The envelope is g(t) = exp −4 ln(2)t 2 /τ 2 , with τ the FWHM, and the number of cycles N c defined by τ = 4π √ ln 2N c /ω. All pulses used satisfy the nonrelativistic criteria 2U p /c 2 1 [31,32] and the dipole condition U p /2ωc…”
mentioning
confidence: 99%